Digital in situ fabrication - Challenges and opportunities for robotic in situ fabrication in architecture, construction, and beyond. (October 2018) - Buchli, Jonas; Giftthaler, Markus; Kumar, Nitish; Lussi, Manuel; Sandy, Timothy; Dörfler, Kathrin; Hack, Norman
Abstract: While a consensus exists that advanced digital and mechatronic technology is on the cusp of profoundly impacting virtually every manufacturing and industry sector, there are some industries that seem to have profited far less from this ongoing 'revolution'. One prominent example of this is the construction sector and, in particular, building construction. In this paper, we aim at discussing some of the reasons for this apparent lack, and some reasons why this might change in the near future. We introduce the problem of digital in situ fabrication as both a significant challenge and a huge opportunity. We support the discussion with an example of a robotically-fabricated digital concrete wall. Overall, we find that solving in situ fabrication constitutes an inherently multidisciplinary challenge.